MicroRNA response to Listeria monocytogenes infection in epithelial cells - Izar, Benjamin; Mannala, Gopala Krishna; Mraheil, Mobarak Abu; Chakraborty, Trinad; Hain, Torsten; Justus Liebig University Giessen (My University, 2012)
MicroRNAs represent a family of very small non-coding RNAs that control several physiologic and pathologic processes, including host immune response and cancer by antagonizing a number of target mRNAs. There is limited knowledge about cell expression and the regulatory role of microRNAs following bacterial infections. We investigated whether infection with a Gram-positive bacterium leads to altered expression of microRNAs involved in the host cell response in epithelial cells. Caco-2 cells were infected with Listeria monocytogenes EGD-e, a mutant strain (Delta inlAB or Delta hly) or incubated with purified listeriolysin (LLO). Total RNA was isolated and microRNA and target gene expression was compared to the expression in non-infected cells using microRNA microarrays and qRT-PCR. We identified and validated five microRNAs (miR-146b, miR-16, let-7a1, miR-145 and miR-155) that were significantly deregulated following listerial infection. We show that expression patterns of particular microRNAs strongly depend on pathogen localization and the presence of bacterial effector proteins. Strikingly, miR-155 which was shown to have an important role in inflammatory responses during infection was induced by wild-type bacteria, by LLO-deficient bacteria and following incubation with purified LLO. It was downregulated following ∆inlAB infection indicating a new potent role for internalins in listerial pathogenicity and miRNA regulation. Concurrently, we observed differences in target transcript expression of the investigated miRNAs. We provide first evidence that L. monocytogenes infection leads to deregulation of a set of microRNAs with important roles in host response. Distinct microRNA expression depends on both LLO and pathogen localization.
Keywords: microRNA; bacterial infection; Listeria monocytogenes; epithelial cells; inflammatory response; ddc:570